Feasibility of a Stop Smoking Program for Healthcare Workers in an Italian Hospital: Econometric Analysis in a Total Worker Health® Approach - Reparata Rosa Di Prinzio; Giorgia Bondanini; Federica De Falco; Maria Rosaria Vinci; Vincenzo Camisa; Annapaola Santoro; Gabriele Arnesano; Guendalina Dalmasso; Massimiliano Raponi; Eugenio Di Brino; Americo Cicchetti; Nicola Magnavita; et al. (Ubiquity Press, 2023)
Background: Over 20% of healthcare workers (HCWs) are active smokers. Smoking is a targeted issue for workplace health promotion (WHP) programs. Objective: Our study aims to evaluate the effectiveness of the Stop Smoking Promotion (SSP) intervention, a 6-hour training course for HCWs, which took place from May 2018 to July 2019. Methods: We compared HCWs who successfully quit smoking (n = 15) to those who did not (n = 25) in terms of Sickness Absence Days (SADs). Moreover, we conducted an econometric analysis by calculating the return on investment and implementing a break-even analysis. Findings: Among the 40 enrolled workers, a success rate of 37.5% was observed after a span of over two years from the SSP intervention (with nurses and physicians showed the best success rate). Overall, participants showed a noticeable absenteeism reduction after the SSP intervention, with a reduction rate of 85.0% in a one-year period. The estimated ROI for the hospital was 1.90, and the break-even point was 7.85. In other words, the organization nearly doubled its profit from the investment, and the success of at least eight participants balanced costs and profits. Conclusion: Our pilot study confirms that WHP programs are simple and cost-saving tools which may help improve control over the smoking pandemic in healthcare settings.